THE USE OF KWL (KNOW, WANT, LEARNED) STRATEGY ON STUDENTS’ READING COMPREHENSION - Dwi Fita Heriyawati; Lulus Irawati; Angellia C.L.T Haliwala (Universitas PGRI Madiun, 2021)
This study aims at investigating the effectiveness of KWL (Know, Want, and Learned) strategy on the students’ reading comprehension. Quasi-experimental design was used in the study. The populationtaken was the seventh grade students of SMP PGRI 6 Malang. There were 54 students belonging to class VII C as the experimental group and VII A as the control group. Both pre and post tests were executed to obtain the data. The primary data were gained by comparing the result of post-test from the experimental group and that of the control group. The result of post-test exhibits that the sig. (2 tailed) or p- value is 0.000 lower than 0.05 (the level of significance). It means that the students who are taught by using KWL strategy have better reading comprehension than those who are not. The results of questionnaire show that the students give very good responses related to the implementation of KWL strategy. Overall, the results imply that the students’ reading comprehension can be effectively increased by using KWL strategy.